Obesity and Maternal-Placental-Fetal Immunology and Health - Monaco-Brown, Meredith; Lawrence, David A. (Frontiers in Pediatrics, 2022)
Obesity rates in women of childbearing age is now at 29%, according to recent CDC reports(1). It is known that obesity is associated with oxidative stress and inflammation, including disruptions in cellular function and cytokine levels. In pregnant women who are obese, associated placental dysfunction can lead to small for gestational age (SGA) infants. More frequently, however, maternal obesity is associated with large for gestational age (LGA) newborns (2), who also have higher incidence of metabolic disease and asthma due to elevated levels of inflammation. In addition, anthropogenic environmental exposures to “endocrine disrupting” and “forever” chemicals affect obesity, as well as maternal physiology, the placenta, and fetal development. Placental function is intimately associated with the control of inflammation during pregnancy. There is a large amount of literature examining the relationship of placental immunology, both cellular and humoral, with pregnancy and neonatal outcomes. Cells such as placental macrophages and NK cells have been implicated in spontaneous miscarriage, preeclampsia, preterm birth, perinatal neuroinflammation, and other post-natal conditions. Differing levels of placental cytokines and molecular inflammatory mediators also have known associations with preeclampsia and developmental outcomes. In this review, we will specifically examine the literature regarding maternal, placental, and fetal immunology and how it is altered by maternal obesity and environmental chemicals. We will additionally describe the relationship between placental immune function and clinical outcomes, including neonatal conditions, autoimmune disease, allergies, immunodeficiency, metabolic and endocrine conditions, neurodevelopment, and psychiatric disorders.